Importance of Diazepam Administration During Electroencephalography in the Differential Diagnosis of Cortical Visual Loss. (January 2014) - Yis, Uluc; Topcu, Yasemin; Bayram, Erhan; Karakaya, Pakize; Cakmakci, Handan; Kurul, Semra Hız
A 14-year-old boy presented with acute visual loss due to cortical blindness. Two weeks after the visual symptoms, the patient developed behavioral abnormalities. Brain magnetic resonance imaging (MRI) revealed hyperintense lesions at parieto-occipital lobes on T2 -weighted and fluid attenuated inversion recovery images. Sleep and awake electroencephalography (EEG) were normal, but diazepam administration revealed bilateral periodic synchronous complexes occurring every 20 to 30 seconds. Elevated measles antibody titers in cerebrospinal fluid confirmed the diagnosis of subacute sclerosing panencephalitis. We conclude that visual loss due to cortical blindness is an important finding of subacute sclerosing panencephalitis. Diazepam administration during EEG should be a part of investigation in cases with unexplained cortical blindness.